2009
DOI: 10.1016/j.stem.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/PI3K/Akt Pathway Regulates the Side Population Phenotype and ABCG2 Activity in Glioma Tumor Stem-like Cells

Abstract: Summary In normal brain, the side population (SP) phenotype is generated by ABC transporter activity and identifies stem cell and endothelial cell sub-populations by dye exclusion. By drug efflux, the ABCG2 transporter provides chemoresistance in stem cells and contributes to the blood brain barrier (BBB) when active in endothelial cells. We investigated the SP phenotype of mouse and human gliomas. In glioma endothelial cells, ABC transporter function is impaired, corresponding to disruption of the BBB in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
641
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 731 publications
(681 citation statements)
references
References 27 publications
32
641
6
2
Order By: Relevance
“…Previous studies have shown that the PI3K/Akt pathway is important for the maintenance of cancer stem-like cells in breast cancer, 41 prostate cancer, 42 medulloblastoma 43 and glioma. 37 In line with these previous observations, our data also demonstrate that the PI3K pathway is critical for stemness of glioma cells. PI3K activity was high in sphere-cultured glioma cells, and inhibition of PI3K activity with LY294002 suppressed the expression of stem cell markers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that the PI3K/Akt pathway is important for the maintenance of cancer stem-like cells in breast cancer, 41 prostate cancer, 42 medulloblastoma 43 and glioma. 37 In line with these previous observations, our data also demonstrate that the PI3K pathway is critical for stemness of glioma cells. PI3K activity was high in sphere-cultured glioma cells, and inhibition of PI3K activity with LY294002 suppressed the expression of stem cell markers.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, inhibition of JNK also decreased mRNA levels of b-catenin in sphere-forming glioma cells (Supplementary Figure S4D). Taken together, these data indicate that JNK signaling is PI3K is an upstream kinase of JNK that governs the self-renewal of glioma stem-like cells As phosphoinoside 3-kinase (PI3K)/Akt pathway has been shown to regulate glioma stemness, 37 we investigated whether this pathway is linked to JNK signaling in the maintenance of stemness of glioma cells. As expected, sphere-forming glioma cells showed significantly higher levels of lipid phosphatase activity and phosphorylated Akt compared with monolayer-cultured glioma cells (Supplementary Figure S5).…”
Section: Inhibitionmentioning
confidence: 99%
“…However, the potential contribution of microglia produced NO to the tumor stem cell phenotype that has yet to be explored. It has also been shown that glioma stem-like cells express multi-drug resistance proteins such as ABCG2 and P-gp (Lu and Shervington, 2008;Bleau et al, 2009;Wang et al, 2010); hence, these cells tend to be highly resistant to cytotoxic drug therapy (Charles and Holland, 2009 (Dix et al, 1999). Signaling through CXCL12-CXCR4 is known to recruit Tregs to bone marrow and may also be involved in the recruitment of Tregs to brain tumors (Zhou et al, 2002;Grauer et al, 2007).…”
Section: Glioma Stem-like Cellsmentioning
confidence: 99%
“…Clinical studies have shown that B50% of these patients die within the first 2 years of therapy (Stupp et al, 2009). Glioma stem-like cells are resistant to temozolomide partly due to elevated MGMT expression (Bleau et al, 2009). Promoter methylation has been shown to be concordant in GBM samples and matching glioma stem cells (Sciuscio et al, 2011); although the effectiveness of temozolomide is not concordant between matched samples.…”
Section: Temozolomidementioning
confidence: 99%
See 1 more Smart Citation